Bridging Asymmetries in Crowdfunding: A Qualitative Review on the Interplay Between Entrepreneurial Signaling and Investor Perception - Selvi Agustina; Ahembang (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review explores the dynamic interplay between entrepreneurial signaling and investor perception in crowdfunding. It examines how various types of signals—such as team credibility, product quality, campaign narratives, and social proof—are interpreted by investors to mitigate information asymmetry. Drawing from recent empirical studies and theoretical advancements, this review highlights that investor decision-making is shaped by both rational evaluation and heuristic processing. Moreover, the study emphasizes the contextual influence of platform design, cultural norms, and emotional cues in shaping investment outcomes. By synthesizing diverse research findings, this paper offers a comprehensive understanding of how signaling strategies influence trust, legitimacy, and funding success in digital entrepreneurial finance. The review contributes to signaling theory and crowdfunding literature by clarifying the psychological and contextual mechanisms that bridge the knowledge gap between entrepreneurs and investors